THE MAJOR ASPECTS IN THE NOTION OF PRAGMALINGUISTICS - Jumamuratova Yulduz Baxtiyarovna (Journals Park Publishing, 2023)
The article below is aimed to analyze aspects of pragmatics: speech acts and conversational implicature, which are the main notions of pragmalinguistics. While delivering a particular speech act, the addressee has some aims to realize and they are called as pragmatic intentions, in this article, the types of these intentions are enumerated and analyzed with samples taken from various texts.
Keywords: pragmalingistic, speech acts, conversational implicature, cooperative principles, maxim of quantity, maxim of quality, maxim of relevance, maxim of manner.